Study of Suicidal Ideation and Attempt among HIV patients in Omdurman National Voluntary Counseling and Testing Centre Khartoum state - Sudan (2021-2022) - Khalil, Mohamed Almostafa AbdAljwad Dahab; Gailani, Aisha Motwakil Bakhiet (Journal of medical and pharmaceutical sciences, 2023)
Background: Suicidal ideation and attempt are more frequent in HIV patients than general populationObjective: The aim of this study was to assess the suicidal ideation and attempt among HIV patients in Omdurman National Voluntary Counseling and Testing Center, Khartoum state, Sudan. Methods: Descriptive cross-sectional institutional based study was conducted among HIV patients attending Omdurman national voluntary counseling and testing Center. Systematic random sampling technique was used to select 235 participants from March to May 2021, data was collected by using a questionnaire consisted of sociodemographic and clinical characteristics and validated tool (Mini international neuropsychiatric interview for suicidality- the Arabic version), data was analyzed using SPSS 26 edition and Chi squire test, the t test and Multivariate test were used for the associations between variablesResults: Suicidal ideation in the last month was (14.5%), suicidal attempt in the last month was (0.4%) and lifetime suicidal attempt was (4.3%). Suicide risk were high in (2.5%), moderate in (10.6%) and low in (12.7%). Marital status, occupation, duration of diagnosis, WHO stages and opportunistic infections were significantly associated with suicidal ideation, whereas opportunistic infections and marital status were significantly associated with suicidal attempt. Conclusion: The suicidal ideation and attempt in the HIV patients in the last month were 14.5% and 0.4% respectively, and the lifetime suicidal attempt was 4.3%. There is significant association between suicidal ideation and attempt and some sociodemographic and clinical characteristics of the patients.
Keywords: Suicidal ideation; Suicidal attempt; HIV; Khartoum state; Sudan